2021
DOI: 10.1093/jscr/rjaa585
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated sigmoid large-cell neuroendocrine carcinoma in an inguinal hernia

Abstract: Large-cell neuroendocrine carcinomas (NECs) of the colon are extremely rare aggressive tumors. A 79-year-old man presented at our hospital for muco-hematic diarrhea, weight loss and incarcerated hernia in his left groin. Colonoscopy revealed sigmoid stenosis. Computed tomography confirmed an incarcerated hernia containing sigmoid mass and massive abdominal adenopathy. In absence of colonic obstruction, the patient underwent elective palliative sigmoid resection and colostomy by laparoscopic approach, and direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…Among the four patients in group B (including the patient in the present case) [ 1 , 11 , 12 ] and 12 patients in group O [ 13 24 ], 10 underwent preoperative colonoscopy, which was not performed in group P. Regarding the usefulness of colonoscopy, Baldi et al [ 15 ] reported that malignancy could be diagnosed before surgery. Gerosa et al [ 14 ] stated that by diagnosing rare neuroendocrine cancers preoperatively, they were able to provide appropriate treatment for a condition with poor prognosis. In addition, Marsden et al [ 24 ] performed colonoscopy in a bilateral hernia patient showing intestinal prolapse and diagnosed cecal cancer within the right hernial sac.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the four patients in group B (including the patient in the present case) [ 1 , 11 , 12 ] and 12 patients in group O [ 13 24 ], 10 underwent preoperative colonoscopy, which was not performed in group P. Regarding the usefulness of colonoscopy, Baldi et al [ 15 ] reported that malignancy could be diagnosed before surgery. Gerosa et al [ 14 ] stated that by diagnosing rare neuroendocrine cancers preoperatively, they were able to provide appropriate treatment for a condition with poor prognosis. In addition, Marsden et al [ 24 ] performed colonoscopy in a bilateral hernia patient showing intestinal prolapse and diagnosed cecal cancer within the right hernial sac.…”
Section: Discussionmentioning
confidence: 99%
“…However, we ultimately opted for the Hartmann procedure because the patient did not consent to a temporary ileostomy. Gerosa et al [ 14 ] reported the only case that involved the Hartmann procedure in the group O. Since their case involved a large-cell neuroendocrine carcinoma, which has an extremely poor prognosis, this procedure may have been performed due to the need to start postoperative adjuvant chemotherapy immediately after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…LCNECC share the same endoscopic and imaging features with colonic adenocarcinomas [ 13 ], often characterized by polypoid masses or ulcerofungating tumors on colonoscopy [ 14 , 15 ], and irregular thickening of the colonic wall or polypoid intramural masses on abdominal tomography [ 13 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Также было доказано, что ранняя ЭПСТ достоверно снижала длительность госпитализации и смертность, что связано со снижением риска развития сепсисассоциированных осложнений, о чем сообщали и другие исследователи [8,10,13].…”
Section: рис 2 Roc-кривая взаимосвязи расчетного и реального риска ра...unclassified
“…При верификации холелитиаза и повышения аланинаминотрансферазы в течение первых 48 часов заболевания у пациентов с тяжелым течением ОП следует заподозрить билиарный панкреонекроз (БПН), при котором все чаще прибегают к интервенционным технологиям [7,8]. Эндоскопические и минимально инвазивные процедуры постепенно завоевывают популярность и широкое распространение в лечении БПН, что дает хорошие результаты с точки зрения безопасности и снижения длительности госпитализации и летальности [9,10].…”
unclassified